Risk stratification for the primary prevention of arrhythmic sudden cardiac death in postinfarction patients: Part I: Prognostic markers reflecting postinfarction fibrosis, abnormal repolarization, and impaired autonomic nervous system function. Issue 3 (September 2016) - Arsenos, P.; Sideris, S.; Gatzoulis, K. A.
Abstract: Sudden cardiac death (SCD) threatens ischemic cardiomyopathy patients. Antiarrhythmic protection may be provided to these patients with implanted cardiac defibrillators (ICD), after an efficient risk stratification approach. The proposed risk stratifier of an impaired left ventricular ejection fraction has limited sensitivity. Current risk stratification strategies focus on markers that, by identifying the arrhythmic substrate and the severity of the arrhythmia mechanisms present, are also considered to quantify the risk of SCD. Such markers reflect: (1) myocardial substrate lesions and postinfarction fibrosis (LVEF, QRS, LBBB, SAECG, fragmented QRS, CMR, PVBs, NSVT), (2) abnormal repolarization (QT, QTd, T‐wave alternans, QT/RR, QTVI, TWV), (3) impaired autonomic nervous system function (HR, heart rate variability (HRV), HRT, deceleration capacity (DC), BRS, HR recovery after exercise), and (4) inducibility on programmed ventricular stimulation during electrophysiological testing. Ventricular tachyarrhythmias have a strong dynamic component because transient and unpredictable factors can trigger a fatal arrhythmic episode. For this reason, SCD risk stratification is not simple and no ideal marker or a completely successful predictive model is existing. The evolution of technology made possible all the noninvasive markers to be incorporated in the Holter software. Noninvasive risk stratification has been simplified. Innovative Holter technology enforced the doctors, providing them with the tools for primarily screening their patients through the ICD protection process. Answer questions and earn CME :https://wileyhealthlearning.com/Activity2/4469459/Activity.aspx